HUBUNGAN RESPONSE TIME DENGAN LUARAN KEBERHASILAN PENANGANAN PERDARAHAN POSTPARTUM DI RSU MARGONO SOEKARDJO PURWOKERTO - Astuti, Dyah Puji; Hakimi, Mohammad; Prawitasari, Shinta (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Maternal mortality rate is still high. PPH is a major cause of maternal mortality in the world and in developing countries. Handling cases of postpartum hemorrhage is right in health facilities can reduce the incidence of maternal death from postpartum hemorrhage cases, therefore, required response time appropriate in health care facilities.This objective of this study is to determine the relationship of response time with the successful outcome of the handling of cases of PPH. An observational study design was used with case-control study design (case control study. The subjects were all mothers who referred to the Hospital of Purwokerto Soekardjo 2008-31Desember from 1 January 2011 due to PPH. Mechanical sampling with purposive sampling . Data collected by observation medical record and in-depth interviews, analysis of the data used to use univariable analysis, and multivariable bivariable.The results of X ² statistical test known value of 0.058 with p 0.810 (OR 1.22 95% CI 0.39 to 3.20) greater that 0.05 is not statistically significant meaning there is no relationship of response time to the successful outcome of treatment of bleeding post partum. Conclusion: There is no relationship of response time with the successful outcome of the handling of cases of postpartum hemorrhage in RSUMargono Soekardjo Purwokerto. Keywords: response time, postpartum hemorrhage